Determination of mercury (II) in water samples by fluorescence using a dansyl chloride immobilized glass slide. Issue 4 (3rd July 2020) - Muhammad, Imran; Muhammad, Turghun; Hoji, Amina; Yang, Xiaoxia; Yigaimu, Aziguli
Abstract: This paper presents the preparation of stable fluorescence sensor slides for Hg 2+ by covalent attachment of a fluorophore which can selectively chelate with the analyte. The fluorophore, dansyl chloride, was immobilized on the glass slide through an amide bond formation reaction with the amino group functionalized on the substrate using 3-aminopropyltriethoxysilane as the salinization agent. The dansyl chloride sensor slide was characterized by Fourier transform infrared (FTIR), ultraviolet-visible and fluorescence spectra. The size of sensor slide was precisely designed to fit in a common cuvette (10 × 10 mm). The ultraviolet-visible absorption and fluorescence response of the sensor to Hg 2+ was directly investigated applying conventional spectrophotometers. The results showed that the sensor fluorescence may be linearly quenched by Hg 2+ across the concentration range from 3.32 × 10 −6 to 26.6 × 10 −6  mol/L in 1:1 acetonitrile:water at pH 7.4. In addition, the sensor showed very high sensitivity to Hg 2+ compared to other metal cations. Furthermore, the sensor slide was successfully applied for the determination of mercury ion in lake water with a recovery from 95.5 to 99.9%. This investigation has demonstrated that the proposed approach may be used to develop a stable, accurate, simple, and selective fluorescence sensor for Hg 2+ .